2015
DOI: 10.1016/j.fertnstert.2015.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Infertility, fertility treatment, and risk of hypertension

Abstract: Objective To evaluate the association between infertility and fertility treatments on subsequent risk of hypertension. Design Cohort Study Setting Nurses’ Health Study II Patients 116,430 female nurses followed from 1993 to June 2011 as part of the Nurses' Health Study II cohort. Intervention None Main Outcome Measures Self-reported, physician diagnosed hypertension Results Compared to women who never reported infertility, infertile women were at no greater risk of hypertension (multi-variable adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
(19 reference statements)
2
22
2
1
Order By: Relevance
“…The study revealed that at a median follow-up of 9.7 years post-delivery, women who had used FTs (n ¼ 6979) had fewer cardiovascular events than those who had not (n ¼ 1,186,753). 8 More specifically studying hypertension, the Nurses' Health Study II, involving 116,430 women, reported that the incidence of hypertension is not higher among women who had previously undergone FT. 44 In contrast, a Swedish study by Westerlund et al found higher rates of hypertension among 23,498 women who had undergone IVF compared with 116,960 individually matched mothers from the Medical Birth Register. 45 One explanation for this could be a baseline difference in incidence or risk factors for hypertension among the sub-fertile population.…”
Section: Long-term Cardiovascular Risk Of Ftsmentioning
confidence: 89%
“…The study revealed that at a median follow-up of 9.7 years post-delivery, women who had used FTs (n ¼ 6979) had fewer cardiovascular events than those who had not (n ¼ 1,186,753). 8 More specifically studying hypertension, the Nurses' Health Study II, involving 116,430 women, reported that the incidence of hypertension is not higher among women who had previously undergone FT. 44 In contrast, a Swedish study by Westerlund et al found higher rates of hypertension among 23,498 women who had undergone IVF compared with 116,960 individually matched mothers from the Medical Birth Register. 45 One explanation for this could be a baseline difference in incidence or risk factors for hypertension among the sub-fertile population.…”
Section: Long-term Cardiovascular Risk Of Ftsmentioning
confidence: 89%
“…In a prior study, attempts were made to elucidate the effect of infertility diagnosis vs infertility treatment by comparing those who reported infertility and received treatment to those who did not; however, the authors were focused on long-term and not pregnancy-specific risks [27]. While it is still unknown whether it is infertility status or infertility treatment that confers increased risk of hypertensive disorders, there are a few hypotheses that could explain the link.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that more than 6 million individuals have been conceived using ART worldwide [81]. Earlier studies did not show an apparent increase in hypertension risk among infertile women or among those with previous fertility treatment [82]. More recently, women who conceived through ART have been shown to be at increased risk of hypertensive disorders in pregnancy.…”
Section: Assisted Reproductive Technologies (Art)mentioning
confidence: 99%